Ecopedagogy Model With Islamic Values Cultivates Student Naturalist Intelligence In Ecosystems: Model Ekopedagogik Nilai Keislaman Menumbuhkan Kecerdasan Naturalis Siswa Pada Pembelajaran Ekosistem - Ferra Yunita; Asrianty Mas’ud; Idad Syuhada (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Educational strategies increasingly prioritize environmental awareness and ecological capacities to ensure sustainable natural habitats. Specific Background In a seventh-grade setting, learners exhibit low ecological empathy and curiosity due to minimal direct interaction with nature, inadequate laboratory facilities, and a reliance on conventional problem-based instruction. Knowledge Gap Although environmental teaching methods exist, their integration with spiritual ethics to foster a holistic sense of ecological responsibility remains under-explored within biological science education. Aims This study investigates the application of an ecopedagogy learning model integrated with Islamic values on the naturalistic intelligence of junior high school pupils during environmental learning. Results Utilizing a quasi-experimental non-equivalent control group design with 48 participants, analysis revealed that the experimental cohort achieved a nine percent pretest-posttest score increase, compared to a five percent increase in the control group. Furthermore, a Mann-Whitney test confirmed statistical significance (p = 0.033), while the calculated effect size (r = 0.307) indicated a small but meaningful practical contribution. Novelty This research uniquely merges an interactive syntax with environmental ethics, specifically framing ecological conservation as a spiritual obligation derived from religious texts. Implications Integrating religious principles within participatory environmental education serves as a highly supportive alternative pedagogical framework for cultivating ecological empathy and sensory awareness. Highlights Pre-test and post-test assessments of seventh-graders revealed a nine percent score progression for the experimental group. The participatory environmental strategy successfully stimulated active classroom involvement and ecological empathy during biological science lessons. Statistical testing utilizing Mann-Whitney procedures confirmed a significance value of 0.033, verifying positive pedagogical outcomes. Keywords Ecopedagogy Learning; Naturalist Intelligence; Islamic Values; Ecosystem Material; Science Education